Agouti Signaling Protein and Its Receptors as Potential Molecular Markers for Intramuscular and Body Fat Deposition in Cattle - Liu, Yinuo; Albrecht, Elke; Schering, Lisa; Kuehn, Christa; Yang, Runjun; Zhao, Zhihui; Maak, Steffen (Frontiers in Physiology, 2018)
Transcriptome analyses of bovine muscle tissue differing in intramuscular fat (IMF) content identified agouti signaling protein (ASIP) as a promising candidate gene for fat deposition. The protein is secreted from adipocytes and may serve as a signaling molecule in cross-talk between adipocytes and muscle fibers or other cells. Known receptors for ASIP are the melanocortin receptors (e.g. MC4R) and attractin (ATRN). The present study was conducted to determine relationships between the expression of ASIP and its receptors in different bovine tissues with fat deposition. Adipose tissues, liver, and longissimus muscle tissue were collected from 246 F2-generation bulls (Charolais × Holstein cross) and gene expression was measured with RT-qPCR. During analysis of subcutaneous fat (SCF) of all bulls, 17 animals were identified with a transposon-derived transcript (Exon2C) inserted in the ASIP gene and dramatically increased ASIP mRNA levels. Significant correlations between normalized mRNA values of SCF and phenotypic traits related to fat deposition were found in bulls without Exon2C. Three retrospectively assigned groups (Exon2C, n = 17; high carcass fat (HCF), n = 20; low carcass fat (LCF), n = 20) were further analyzed to verify expression differences and elucidate molecular reasons. Expression of ASIP could be detected in isolated muscle fibers and adipocytes of Exon2C bulls in contrast to HCF and LCF bulls, indicating ectopic ASIP expression if the transposon is present. Among adipose tissues, highest ASIP mRNA levels were measured in SCF with significantly higher values in HCF compared to LCF bulls (1.6-fold, P < 0.05). However, the protein abundance was below the detection limit in all bulls. Potential ASIP receptors were detected in most investigated tissues. The expression of MC4R was higher and of ATRN was lower in several tissues of LCF compared to HCF bulls, whereas MC1R was not differentially expressed. Bulls of the Exon2C group had lower ATRN mRNA values than HCF and LCF bulls in perirenal fat (PF), but higher (P < 0.05) values in muscle. Receptors were also expressed in tissues where ASIP mRNA was not detected. Consequently, those tissues could be targets for ASIP if it circulates.